The silent threat of sharp food injury: eggshell-associated acute epiglottitis in an adult - Ahmad Shukri, Fatin Aisya; Mohamad, Adam; Johari, Ahmad Hafizuddin (Elsevier, 2026)
Adult epiglottitis is a potentially life-threatening condition that may present without overt airway compromise. Trauma-induced supraglottitis from sharp food particles is uncommon but clinically significant. We report a 47-year-old man who developed progressive odynophagia, dysphagia and muffled voice two days after ingesting an eggshell fragment. He remained haemodynamically stable without stridor. Indirect laryngoscopy revealed a markedly oedematous and erythematous epiglottis with complete obliteration of the valleculae and slough over the base of tongue. Lateral neck radiograph demonstrated the classical thumb sign. Laboratory findings showed neutrophilic leukocytosis and elevated inflammatory markers. A diagnosis of trauma-induced acute epiglottitis was made. The patient was admitted for close airway monitoring and treated with intravenous ampicillin–sulbactam and dexamethasone, resulting in rapid clinical and endoscopic resolution. This case highlights that even minor mucosal injury from an eggshell fragment can precipitate significant supraglottic inflammation, underscoring the importance of early endoscopic evaluation and prompt management to prevent airway compromise.